Apelin and G212A apelin receptor gene polymorphism in obese and diabese youth. Issue 3 (24th July 2014) - Kotanidou, E. P.; Kalinderi, K.; Kyrgios, I.; Efraimidou, S.; Fidani, L.; Papadopoulou‐Alataki, E.; Eboriadou‐Petikopoulou, M.; Galli‐Tsinopoulou, A.
Summary Objective The apelinergic system has been previously described to participate in fluid homeostasis, cardiac contractility, blood pressure and neo‐vascularization. The role of apelin in obesity and glucose metabolism has also lately gained interest; however, it still remains obscure. This study aimed to assess serum apelin levels in obese youngsters and to investigate any possible association with the G212A polymorphism of the apelin receptor (APLNR) gene. Methods Ninety obese individuals and 90 matched for age and gender lean controls were included. Anthropometric measurements, data of glucose metabolism, including an oral glucose tolerance test, and serum apelin levels were obtained. The presence of the G212A polymorphism of the APLNR gene was also analyzed in the obese group. Results Obese participants had significantly lower serum apelin levels as compared with controls (P = 0.011). After being grouped according to their status of glucose metabolism, only obese subjects with impaired glucose metabolism (diabese) exhibited lower apelin levels as compared with controls. The presence of the G212A polymorphism did not differ from the HapMap‐reported frequencies in Caucasians (GG = 53.3%/GA = 38.9%/ΑΑ = 7.8% vs. GG = 46.9%/GA = 39.8%/ΑΑ = 13.3%, P = 0.232). The GG and GA obese subgroups had significantly lower apelin levels as compared with the AA group (P = 0.013 and P = 0.016, respectively). Conclusion Obese (especially diabese) youngsters demonstrated lower serum apelin levels; the G212A polymorphism of the APLNR gene was found to exert a favourable effect on circulating apelin levels in childhood obesity.